The networked city - Raf Verbruggen; Michael Hoyler; Peter J. Taylor (2014)
After the demise of the western Roman Empire in the 5th century, urban growth came to a standstill in most parts of western Europe. Only in the course of the 11th century did a new phase of urbanization begin. Although improvements in agriculture played a significant part in this urban renewal, it was primarily the revival of trade – especially with the more developed and urbanized economies of the Near East in the wake of the crusades – that caused cities to spring up again in many parts of Europe. The development of strong trade links between the cities of Latin Christian Europe (which were further intensified as a consequence of the commercial revolution of the 13th century) warrants the introduction of a specific typology to describe the late medieval and 16th-century European city: the networked city.